The Impact of E-Commerce Online Loans on Mental Health Among Young Adults: Retail Therapy or Financial Stress? - Brain Kaparang; Grace Fresania Kaparang (Jurnal Economic Resource, 2026)
The rapid growth of e-commerce and fintech lending services has transformed consumer behavior globally. Online loan systems, particularly Buy Now Pay Later (BNPL) and digital credit facilities integrated into e-commerce platforms, provide immediate purchasing power and financial accessibility. The rapid expansion of fintech lending systems, Buy Now Pay Later (BNPL) services, and digital shopping platforms has transformed consumer purchasing behavior globally. While online loans provide convenience and short-term financial flexibility, excessive borrowing behavior has increasingly been associated with psychological distress, compulsive shopping, financial stress, anxiety, depression, and psychosocial dysfunction. This study aims to examine the relationship between e-commerce online loan usage and mental health outcomes, specifically investigating whether online borrowing behaviors function as a form of retail therapy or contribute to financial stress among young adults. This systematic literature review (SLR) examines the relationship between online loans, e-commerce behavior, and mental health outcomes. Using PRISMA 2020 guidelines, this review synthesized evidence from Scopus, ScienceDirect, PubMed, Google Scholar, and SpringerLink. The findings of 17 eligible articles demonstrate that impulsive buying behavior, social media influence, consumerism, emotional purchasing motivations, and low financial literacy significantly contribute to problematic online borrowing behavior. Furthermore, financial stress, debt burden, social stigma, and aggressive debt collection practices negatively affect mental health and psychosocial well-being. Protective factors such as financial literacy, emotional regulation, self-control, social support, and responsible borrowing behavior were identified as important moderators of psychological outcomes. This review highlights the need for integrated financial literacy programs, mental health interventions, and stronger fintech regulations to reduce the harmful effects of online loan dependency. Although online loans may offer temporary emotional satisfaction, long-term dependency on digital borrowing is more strongly associated with adverse mental health consequences. Strengthening financial literacy, responsible lending regulations, and psychological support systems is necessary to reduce the harmful psychosocial impact of e-commerce online loans.